2017
DOI: 10.1088/0253-6102/68/3/285
|View full text |Cite
|
Sign up to set email alerts
|

Qubit Systems from Colored Toric Geometry and Hypercube Graph Theory *

Abstract: We develop a new geometric approach to deal with qubit information systems using colored graph theory. More precisely, we present a one to one correspondence between graph theory, and qubit systems, which may be explored to attack qubit information problems using toric geometry considered as a powerful tool to understand modern physics including string theory. Concretely, we examine in some details the cases of one, two, and three qubits, and we find that they are associated with CP1, CP1 × CP1 and CP1 × CP1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…It has been shown that the first factor SO(4,20) SO( 4)×SO (20) represents the geometric deformations of the K3 surface in the presence of the antisymmetric B-field of the NS-NS sector and it is linked to the symmetry group G 1 = U (1) 24 . However, the second factor SO(1, 1) represents the dilaton scalar field which is associated with G 2 = U (1) [35,36].…”
Section: Dyonic Solutions In Type II Superstringsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the first factor SO(4,20) SO( 4)×SO (20) represents the geometric deformations of the K3 surface in the presence of the antisymmetric B-field of the NS-NS sector and it is linked to the symmetry group G 1 = U (1) 24 . However, the second factor SO(1, 1) represents the dilaton scalar field which is associated with G 2 = U (1) [35,36].…”
Section: Dyonic Solutions In Type II Superstringsmentioning
confidence: 99%
“…The main obtained relations are between the entropy formulas for specific black hole solutions in supergravity theories and entanglement measures for certain multiqubit systems [17,18]. Alternative studies have been conducted using toric geometry and graph theory [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations on CP 2 in [9] were aimed at evaluating the Aharonov-Anandan phase for a 3-state spin-1 system using the Kähler connection. More recently there have been interesting applications using ideas from toric geometry [23]. In this paper we shall further elaborate on applications of this formalism, including the study of the quantum entanglement of qubits.…”
Section: Jhep01(2016)135mentioning
confidence: 99%
“…Concretely, a remarkable correspondence between qubit systems and black holes in superstring theory has been established. The relevant findings concern a nice link between the N = 2 STU black hole with eight charges and threequbit system states [13,17,18,19]. The analysis has been developed to describe structures going beyond such extremal black hole solutions in terms of higher dimensional qubit systems.…”
Section: Introductionmentioning
confidence: 99%